Evidence of Itinerant Ferromagnetism in Transition Metal Doped ZnO Nanostructures - V. Bandyopadhyay; K. Bhushan; S. Mukherjee (Журнал нано- та електронної фізики)
This work is aimed at synthesizing and characterizing transition metals (Mn, Fe and Ni) doped ZnO nanostructures. The samples have been prepared by chemical co-precipitation method. The samples have been divided and one half has been coated SiO2. X-Ray diffraction indicated the formation of single phase ZnO. Optical and photoluminescence studies have been carried out using UV-Vis spectroscopy and Photoluminescence spectroscopy respectively. Magnetic responses of the samples have been studied using SQUID. The structural studies revealed that sample is having wurzite structure at room temperature. Magnetization results shows the ferromagnetism in 2  Fe doped, 5  Ni doped and 2  Mn doped ZnO.